PARENTING MODEL OF ISLAMIC RELIGIOUS EDUCATION IN STRENGTHENING OF THE NATION 'S CHARACTER - Imam, Muhayat (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This research explores the Polytechnic for land transport (Poltrada) Bali on the parenting model of Islamic Religious Education (PAI) learning. This means encouraging generations to take responsibility for what they do, open communication full of politeness, caregivers still respect the efforts made by Taruna, caregivers understand the emotions each Taruna has. Taruna-Taruni can freely express their opinions. However, caregivers demand, as well as give freedom to express their creations in a responsible way. All of that is applied in PAI learning. Poltrada Bali was founded in 2002 under the name BPPTD Bali. BPPTD became the Polytechnic for Land Transport (Poltrada) Bali referring to Minister Regulation Number 30 in 2019. The Bali Poltrada emphasizes the process of training lectures. Islamic Religious Education (PAI) lectures also lead to practical learning. The PAI learning model implemented at the Poltrada Bali, aims to improve the quality of learning aimed at, among other things: achievement planning, strategy, evaluation, and new qualities that can be achieved in PAI learning. As with the parenting pattern that has been applied by Poltrada, Bali. This research uses the R&D research method, research by constructing a series of activities carried out by the Bali Police to innovate using research techniques to solve problems or learn new things. With the parenting model in PAI learning, good qualifications show that the learning process to the results of the assessment is well organized and convincing facts are obtained to support the conclusion of obtaining good grades. Whereas in the very good category it shows that it is organized by presenting facts supported by examples that have been analyzed according to the concept. The fact was found that the model applied to PAI learning obtained very good grades. This normative internalization qualification directly from an early age has become the character of the Taruna Poltrada Bali and can develop and play the nation's character.